Correction: South African Renal Registry Annual Report 2015 - kidney transplants in KwaZulu-Natal - Hariparshad, Sudesh (African Journal of Nephrology, 2017)
This correction serves to update the reported numbers of new kidney transplants performed annually since 2012 in the public sector in the province of KwaZulu-Natal.